Variations in functional and morphological characteristics of elite polish field hockey players in a complete macrocycle - Konarski, J.; Krzykala, M.; Podgórski, T.; Pawlak, M.; Strzelczyk, R.; Malina, R. M. (International Journal of Sports Science and Coaching, 2012)
The purpose was to evaluate a hypothesized model of change during a training and competition macrocycle in a sample of elite field hockey players. Subjects were 11 members of the Polish national team. Players were measured and tested four times through a complete macrocycle. Variables included body mass, % Fat (BIA), aerobic endurance, maximal running speed, speed-endurance and blood lactate concentrations after the endurance, speed and speed-endurance tests. Significant changes occurred in % Fat, aerobic endurance and blood lactate concentrations at different phases of the macrocycle. Mean changes for the total sample did not follow the hypothesized model for speed, aerobic endurance and speed-endurance between specific periods of the macrocycle. Variability among individual players was considerable and emphasized the importance of individualizing training protocols during a macrocycle. The results highlighted the need to consider specific functional capacities (speed, aerobic endurance, speed-endurance) of individual athletes in addition to technical and tactical skills.